Distribusi Margin Pemasaran dan Efisiensi Rantai Pemasaran Bawang Putih di Kabupaten Karanganyar - Hanifah Putrirahmah Ningrum; Endang Siti Rahayu; Setyowati Setyowati (Universitas Proklamasi 45, 2026)
This study analyzes the distribution of marketing margins and the efficiency of the garlic marketing chain in Karanganyar Regency. Data were collected through surveys of farmers and marketing intermediaries and analyzed using marketing margin, farmer’s share, and profit–cost ratio approaches. The results show that marketing margins vary across marketing channels and tend to increase with longer distribution chains. Higher farmer’s share values were found in shorter marketing channels, indicating a more farmer-oriented price distribution. All marketing channels have profit–cost ratios greater than one, indicating that marketing activities are economically feasible, although efficiency levels vary among channels. Overall, the garlic marketing chain in Karanganyar Regency is dominated by relatively long channels, resulting in uneven margin distribution. Strengthening farmer institutions and shortening the marketing chain are recommended to improve marketing efficiency and price distribution fairness.